Ben is back - Hedges, Peter; Roberts, Julia, 1967-; Hedges, Lucas, 1996-; Vance, Courtney B. (Santa Monica, California : Lionsgate, 2019)
When a drug addict surprises his family by returning home on Christmas Eve, he and his mother realize that they must rebuild their relationship.
Originally released as a motion picture in 2018.
Wide screen 1.85:1.
Julia Roberts, Lucas Hedges, Courtney B. Vance, Kathryn Newton, Rachel Bay Jones.
MPAA rating: R.
In English with optional English or Spanish subtitles.
Closed-captioned.
Keywords: Mothers and sons -- Drama; Families -- Drama; Drug addicts -- Drama; Christmas plays; Fiction films; Video recordings for the hearing impaired; Feature films